Ministerial Decree Nos 979 And 1002/2014 Amending some provisions of the tourism Legislations = القرارين الوزاريين رقمي 979 و 1002 لسنة 2014 بتعديل بعض أحكام التشريعات السياحية / Ministry of Tourism - Egypt. Ministry of Tourism (2025)
Ministry of tourism decree no. 979 of the year 2014 issued on 19/11/2014 -- Ministry of tourism decree no. 1002 of the year 2014 issued on 24/11/2014 وزارة السياحة قرار رقم 979 لسنة 2014 صادر بتاريخ 19/11/2014 -- وزارة السياحة قرار رقم 1002 لسنة 2014 صادر بتاريخ 24/11/2014